Extracellular lipids of Candida albicans biofilm induce lipid droplet formation and decreased response to a topoisomerase I inhibitor in dysplastic and neoplastic oral cells - Freddy Humberto MARIN-DETT; Jonatas Erick Maimoni CAMPANELLA; Eliane TROVATTI; Maria Célia BERTOLINI; Carlos Eduardo VERGANI; Paula Aboud BARBUGLI (University of São Paulo, 2023)
Abstract Objective Some microorganisms, i.e., Candida albicans, have been associated with cancer onset and development, although whether the fungus promotes cancer or whether cancer facilitates the growth of C. albicans is unclear. In this context, microbial-derived molecules can modulate the growth and resistance of cancer cells. This study isolated extracellular lipids (ECL) from a 36-h Candida albicans biofilm incubated with oral dysplastic (DOK) and neoplastic (SCC 25) cells, which were further challenged with the topoisomerase I inhibitor camptothecin (CPT), a lipophilic anti-tumoral molecule. Methodology ECL were extracted from a 36-h Candida albicans biofilm with the methanol/chloroform precipitation method and identified with Nuclear Magnetic Resonance (1H-NMR). The MTT tetrazolium assay measured ECL cytotoxicity in DOK and SCC 25 cells, alamarBlue™ assessed cell metabolism, flow cytometry measured cell cycle, and confocal microscopy determined intracellular features. Results Three major classes of ECL of C. albicans biofilm were found: phosphatidylinositol (PI), phosphatidylcholine (PC), and phosphatidylglycerol (PG). The ECL of C. albicans biofilm had no cytotoxic effect on neither cell after 24 hours, with a tendency to disturb the SCC 25 cell cycle profile (without statistical significance). The ECL-induced intracellular lipid droplet (LD) formation on both cell lines after 72 hours. In this context, ECL enhanced cell metabolism, decreased the response to CPT, and modified intracellular drug distribution. Conclusion The ECL (PI, PC, and PG) of 36-h Candida albicans biofilm directly interacts with dysplastic and neoplastic oral cells, highlighting the relevance of better understanding C. albicans biofilm signaling in the microenvironment of tumor cells.